LaTeX cookbook : over 90 hands-on recipes for quickly preparing LaTeX documents to solve various challenging tasks /: over 90 hands-on recipes for quickly preparing LaTeX documents to solve various challenging tasks. (2015) - Kottwitz, Stefan
No abstract available